Juvenile Idiopathic Arthritis: A Study of 74 Cases in Northeast Brazil - Catarina Fernandes Pires; Ana Carolina Santos Londe; Anália Fernandes Pires; Lúcio Fernandes Pires; Maria do Socorro Teixeira Moreira Almeida; Joemir Jabson da Conceição Brito; Manoel Barros Bértolo (Journal of Advanced Rheumatology Science, 2017)
Objectives: To identify the clinical epidemiological characteristics of patients with juvenile idiopathic arthritis (JIA) monitored at the Lucidio Portella Children’s Hospital (HILP) in northeastern Brazil and to ascertain the frequency and forms of presentation, the most affected joints, the most common joint involvement for each form, the frequencies of positive rheumatoid factor (RF+) and positive antinuclear antibodies (ANA+) in the various forms of presentation, and the most common complications. Methods: A study was conducted with 74 medical records of patients with JIA monitored at HILP between January 2010 and January 2013. Descriptive statistics were used for statistical analysis. Results: JIA was predominant in females with a mean age at onset of 5.2 years and a median disease duration of two years. The most frequent initial form of presentation was oligoarticular (63.5) arthritis, and the most affected joint was the knee (86.4%). The knee was most affected by oligoarticular arthritis, the wrist, knee, and ankle were affected by RF+ polyarticular arthritis, and the knee, ankle, and cervical spine were affected by systemic arthritis. RF+ was observed in 8.5% of the oligoarticular arthritis cases. ANA+ were present in 27.7% of the oligoarticular cases, in 22.2% of the systemic arthritis cases, and in 11.1% of the RF+ polyarticular arthritis . The most common complications were deformities (20.3%) and uveitis (14.9%). Conclusion: The findings for JIA patients in a referral hospital in northeastern Brazil were consistent with the literature regarding most of the evaluated criteria.
Keywords: Juvenile Idiopathic Arthritis